PENGEMBANGAN LKPD BERORIENTASI EKSPERIMEN DALAM PEMBELAJARAN TEMATIK TERPADU DI SEKOLAH DASAR - Sri Mulyani; Farida F (Universitas Pahlawan Tuanku Tambusai, 2020)
One effort to improve the quality of education in Indonesia is through efforts to improve teaching and learning at all levels of education. The 2013 curriculum uses an integrated thematic learning approach from class I to class VI. Integrated thematic learning emphasizes student involvement in learning. One way that must be done by teachers in integrated thematic learning, especially in making LKPD is to have to link the material to the real situation of students in life in the community where they will work and live life, namely learning by using experimental methods in the learning process.This study aims to develop learning tools for thematic-oriented experiments in the form of lesson plans, student books, and student worksheets that are valid, practical, and effective.This equipment was developed using a four-D model. Spread not done. Data collection is done by validating and trying out the tools developed. The equipment design has been designed, validated by three experts and practices and then limited tested in class IV of SDN Dadok Tunggul Hitam Padang to determine the alignments and effectiveness of the equipment developed. From the results of this research, it can be seen that experimental learning oriented science equipment for elementary school consisting of lesson plans, and student worksheets has a very valid category. Based on limited tests, it can be seen that the implementation has a good category. Teacher and student responses after using this learning tool showed positive results where the average response was appropriate. Monitoring student activities is very high. Cognitive, affective, and motoric assessments show more completeness than the minimum standard. The conclusion of this study is that science-oriented experimental equipment for elementary schools is declared to be very valid, practical and effective.